How Do People in MENA Evaluate their Economic Prospects? - Mottaghi, Lili (World Bank, Washington, DC, 2016)
In the global environment with the risk of prolonged low growth, the short-term economic outlook for the Middle East and North Africa (MENA) region remains “cautiously "pessimistic”, according to the World Bank’s latest MENA Economic Monitor. Growth in theregion is expected to average about 3 percent i